2014
DOI: 10.1371/journal.pone.0091768
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Mechanism of β-Aminobutyric Acid-Induced Resistance in Wheat to the Grain Aphid, Sitobion avenae

Abstract: The non-protein amino acid β-aminobutyric acid (BABA) can induce plant resistance to a broad spectrum of biotic and abiotic stresses. However, BABA-induced plant resistance to insects is less well-studied, especially its underlying mechanism. In this research, we applied BABA to wheat seedlings and tested its effects on Sitobion avenae (F.). When applied as a soil drench, BABA significantly reduced weights of S. avenae, whereas foliar spray and seed treatment had no such effects. BABA-mediated suppression of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Consistent with our findings, no appreciable influences on herbivores mortality were reported upon applying the studied inducers (Plymale et al 2007;Uefune et al 2013). Similar to our laboratory bioassay, Cao et al (2014) recently found that Sitobion avenae (F.) could not discriminate an artificial diet containing BABA from the standard diet, indicating that BABA itself is not a deterrent to this aphid, which evidences that the poor performance of herbivores upon inducer treatment is due to the activation of an elicitor-induced plant defense.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with our findings, no appreciable influences on herbivores mortality were reported upon applying the studied inducers (Plymale et al 2007;Uefune et al 2013). Similar to our laboratory bioassay, Cao et al (2014) recently found that Sitobion avenae (F.) could not discriminate an artificial diet containing BABA from the standard diet, indicating that BABA itself is not a deterrent to this aphid, which evidences that the poor performance of herbivores upon inducer treatment is due to the activation of an elicitor-induced plant defense.…”
Section: Discussionsupporting
confidence: 80%
“…Ten days after treatment, Cao et al. () still observed the presence of BABA in wheat phloem sap. Hodge et al.…”
Section: Discussionmentioning
confidence: 99%
“…BABA treatment on citrus reduced the infestation of the Asian citrus psyllid, Diaphorina citri Kuwayama (Tiwari et al., ). BABA effectively protected soybean from Aphis glycines Matsumura infestation (Zhong et al., ) and BABA application on wheat seedlings reduced weight of the grain aphid, Sitobion avenae (Fabricius) (Cao et al., ). In some cases, the observed reduced infestation was correlated with the priming of plant defences (Tiwari et al., ; Zhong et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When applied on citrus, BABA was reported to citrus resistance to the Asian citrus psyllid, Diaphorina citri (Tiwari et al, 2013). Cao et al (2014) suggested that mechanism of BABA-induced resistance in wheat to the grain aphid, Sitobion avenae is associated with direct toxicity of high BABA contents in plant phloem. Further study was needed to determine the role of amino acids contents in aphid suppression of the compost extract.…”
Section: Discussionmentioning
confidence: 99%